Madhuritole in Rupandehi, Nepal - CGIAR Research Program on Climate Change, Agriculture and Food Security (2011)
Photos taken from the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) research benchmark site in Rupandehi, Nepal.